A Small, Calibrated Macromodel to Support Inflation Targeting at Norges Bank - Tore Anders Husebø; Sharon McCaw; Kjetil Olsen; Øistein Røisland (Norges Bank, 2004)
This note outlines a small, calibrated macromodel that can be used to support inflation targeting at Norges Bank. The model provides a stylised representation of the key flows in the macro economy, with a particular emphasis on the transmission mechanism of monetary policy. It can be viewed as the minimal model necessary to explain the nexus of output, interest rates, exchange rates and inflation, with a framework for the way monetary policy influences the real economy and inflation. The model should be viewed mainly as a pedagogical device and as a pilot model for subsequent model development at Norges Bank.
hdl:11250/2508141
Keywords: 330